Pseudomonas aeruginosa-Derived Volatile Sulfur Compounds Promote Distal Aspergillus fumigatus Growth and a Synergistic Pathogen-Pathogen Interaction That Increases Pathogenicity in Co-infection - Scott, Jennifer; Sueiro-Olivares, Monica; Ahmed, Waqar; Heddergott, Christoph; Zhao, Can; Thomas, Riba; Bromley, Michael; Latgé, Jean-Paul; Krappmann, Sven; Fowler, Stephen; Bignell, Elaine; Amich, Jorge (Frontiers in Microbiology, 2019)
Pathogen-pathogen interactions in polymicrobial infections are known to directly impact, often to worsen, disease outcomes. For example, co-infection with Pseudomonas aeruginosa and Aspergillus fumigatus, respectively the most common bacterial and fungal pathogens isolated from cystic fibrosis airways, leads to a worsened prognosis. Recent studies of in vitro microbial cross-talk demonstrated that Pseudomonas aeruginosa-derived volatile sulphur compounds (VSCs) can promote Aspergillus fumigatus growth in vitro. However, the mechanistic basis of such cross-talk and its physiological relevance during co-infection remains unknown. In this study we combine genetic approaches and GC-MS-mediated volatile analysis to show that A. fumigatus assimilates VSCs via cysteine (CysB)- or homocysteine (CysD)-synthase. This process is essential for utilisation of VSCs as sulphur sources, since P. aeruginosa-derived VSCs trigger growth of A. fumigatus wild-type, but not of a ΔcysBΔcysD mutant, on sulphur-limiting media. P. aeruginosa produces VSCs when infecting Galleria mellonella and co infection with A. fumigatus in this model results in a synergistic increase in mortality and of fungal and bacterial burdens. Interestingly, the increment in mortality is much greater with the A. fumigatus wild-type than with the ΔcysBΔcysD mutant. Therefore, A. fumigatus’ ability to assimilate P. aeruginosa derived VSCs significantly triggers a synergistic association that increases the pathobiology of infection. Finally, we show that P. aeruginosa can promote fungal growth when growing on substrates that resemble the lung environment, which suggest that this volatile based synergism is likely to occur during co-infection of the human respiratory airways.